Persepsi pentadbir sekolah dan guru-guru terhadap perkhidmatan bimbingan dan kaunseling di sekolah-sekolah menengah di bahagian Kuching dan Samarahan - Mohamad, Bin Obey. (1998)
This study identifies the perceptions of school administrators and teachers towards the implementation of guidance and counseling services in secondary schools in Kuching and Samarahan Division, Sarawak. It focuses on (1) the knowledge and experiences of school administrators and teachers on guidance and counseling services in schools; (2) the perceptions of school administrators and teachers towards ten guidance and counseling services; (3) the perceptions of school administrators and teachers towards the implementation of 10 guidance and counseling services; and (4) the perceptions of school administrators and teachers towards implementation of career guidance and counseling activities in schools. Research samples comprise 140 people, of which 40 are school administrators and 100 are teachers, from 10 secondary schools.